PENGARUH LOKASI DAN KEUNGGULAN BERSAING TERHADAP LOYALITAS PELANGGAN DI A DUA COFFEE MEDAN - Mei Hendrik Harianto Lafau; Idahwati Idahwati (JURNAL MUTIARA MANAJEMEN, 2020)
The backround of this research is by the growth rate of cafes in the city of Medan which is quite rapid, thus increasing the rivalry between cafes, where each cafe tries to prepare the best strategy to make loyal customers and want to visit again. The method of this research is quantitative to get data and the information that will be use as the analysis language. The sample of this research is 60 peoples. The data collection technique is us the distribution of questionnaires to customers in “A Two Coffe Medan”. The aims of the research is (1) To determine the effect of location on customer loyalty in “A Dua Coffe Medan”, (2) To determine the effect of competitive advantage on customer loyalty in “A Dua Coffe Medan”, (3) To determine the effect of location and competitive advantage on customer loyalty in “A Dua Coffe Medan”. The results of this research will show that: tcount > ttable 3,353 > 1,672 with significant a (0.001 < 0,05), (2) there is the effect of competitive advantage on customer loyalty with value : : tcount > ttable 2,074 > 1,672 with significant a (0.000 < 0,05), (3) there is the effect of location and competitive advantage on customer loyalty with value : : fcount > ftable (53,508 > 3,16) with significant a (0.000 < 0,05).